Multi-path Data Transmission to Protect Data in Transit - Court, Andrew; Alamleh, Hosam (Proceedings of IEEE International Symposium on Consumer Electronics, 2023)
In the last few decades, society has seen rapid advancements in Information and Communications Technology (ICT), which have revolutionized how data is created, transmitted, stored, and exchanged. ICT is a vast and everchanging subject, but two important concepts derived from ICT are data communications and networking. Data communications involve the use of a transmission medium, wired or wireless, to allow for the exchange of data between two or more devices. Many of the applications people rely on today require the use of data, including personal data, and thus, are enabled by data communications. Increased efficiency and speed of data communication have seen paralleled increases in the field of communication surveillance. When it comes to data transmission, surveillance is of the utmost importance. However, how data during transmission is protected is a topic that requires endless exploration. This paper begins with a discussion of ICT and how it has evolved within society today. Next, surveillance techniques for data transmission are explored, followed by counter-surveillance techniques to deter potential hackers from accessing private data. During the discussion of counter-surveillance, a novel counter-surveillance technique is proposed. This technique centers around directing traffic from the transmitting side over multiple links to the receiving side, resulting in data aggregation. Utilizing a powerful packet manipulation tool, Scapy, along with raw socket programming using the Python programming language, this paper presents, implements, tests, and evaluates a proof of concept for the proposed system. Using a stable Wi-Fi connection and a mobile hotspot as the two-multimedia links, with segments being sent in on alternating links, secure and successful data transmission from the client side to the server side was achieved.